The role of lipid peroxidation and antioxidant protection in skin in the development of experimental contact dermatitis - Regeda-Furdychko, M. M. (Journal of Education, Health and Sport, 2020)
The purpose of work to study the conditions of prooxidant and antioxidant system in the skin of guinea pigs in different periods of contact dermatitis formation. Materials and methods. Researches were conducted on guinea pigs, divided into five groups: I - control, II – 4th day of expirement, III – 8th day of contact dermatitis development, IV – 10th day and V - 18 th day of model process. Early period included groups of animals on the 4th and 8th days of experiment. The late one – guinea pigs on the 10th and 18th days of contact dermatitis. Experimental contact dermatitis was simulated by method of Volkovoj V. A. (2010). Condition of free radical lipid oxidization in the skin was determined on maintenance content of malonic dialdehyde by method of Corobeynikov E. G. (1989) and diene conjugates by method of Gavrylov V. G., Myshkorudna M. I. (1989). The degree of activity of antioxidant defence was estimated on maintenance enzymes - superoxidedismutase by method of R. Fried (1975), catalase by the method of B. Holmes, C. Masters (1970), glutationperoxidase method of Arkhipova O. G. (1988) and glutationreductase method of Moina V. M. (1986). Results and discussion. Gradual increasing of lipid peroxydations products - malonic dialdehyde, diene conjugate had been determined on the 4th, 8th, 10th and 18th days of experimental contact dermatitis development in this research. Primary increasing of the indices of superoxidedismutase, glutationreductase, glutationperoxidase and catalase has been investigated in the skin on the 4th day with the following decreasing of these enzymes from the 8th day of experiment. It testified about imbalance in antioxidant and prooxydant systems, especially on the 10th and 18th days of the study, which exacerbates the inflammatory process in the skin and also triggers a cascade of other mechanisms of damage.